Search for long-lived particles decaying to jet pairs - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (The European physical journal. C, Particles and fields, 2015)
A search is presented for long-lived particles with a mass between 25 and 50 $$\mathrm{GeV}/\mathrm{c}^{2}$$and a lifetime between 1 and 200$$\mathrm{\,ps}$$in a sample of proton-proton collisions at a centre-of-mass energy of $$\sqrt{s}=7$$ TeV, corresponding to an integrated luminosity of 0.62 $$\text{ fb }^{-1}$$, collected by the LHCb detector. The particles are assumed to be pair-produced by the decay of a standard model-like Higgs boson. The experimental signature of the long-lived particle is a displaced vertex with two associated jets. No excess above the background is observed and limits are set on the production cross-section as a function of the long-lived particle mass and lifetime.
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, O. Grünberg, X. Han, S. Hansmann-Menzemer, M. Heß, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 662 weitere]
Gesehen am 26.07.2021